Identification of inhibitory mechanisms preventing CENP-A assembly in the S phase of the cell cycle - Abreu, Rúben Lopes Pereira (2016)
Tese de mestrado, Biologia Evolutiva e do Desenvolvimento, Universidade de Lisboa, Faculdade de Ciências, 2015